SAT0288 Eosinophilic Granulomatosis with Poliangeitis (EGPA): Clinical Features and Outcome in A Large Serie of Spanish Patients. (10th June 2014) - Solans-Laqué, R.; Fraile, G.; Castillo, M.J.; Solanich, X.; Caminal, L.; Rodriguez, M.; Rios, J.J.; Zamora, M.; Calleja, J.L.; Fanlo, P.; Garcia, I.; Saez, L.; et al.
Abstract : Objectives: To analyze the demographic, clinical, laboratory features and outcome of patients with EGPA in a large cohort of Spanish patients with AAV Methods: multicenter retrospective-longitudinal study that included patients diagnosed with AAV between January 1995 and December 2012 in 19 Hospitals from Spain (REVAS Study). Statistical analysis was performed using the SPSS vs17. Results: 87 patients with EGPA (mean age 52.5±16.1 yr) from 405 with AAV were analyzed. Asthma was present in all cases and preceded EGPA by 6 months to 29 yr (mean 81.6 mo) except in 6 cases in which began simultaneously. A history of allergic rhinitis was noted in 42.5% cases with nasal polyposis in 23% and recurrent sinusitis in 49.4%. ANCA were positive in 66% cases (91% MPO ANCA). Mean follow-up was 82.5±75.3 months. The most frequent clinical manifestations at diagnosis were fever (44%), arthralgia (47%), constitutional symptoms (41%), neurological symptoms (54%), and purpura (35%). Renal failure was present in 14% cases, reno-pulmonary sd. in 4.6% and cardiac involvement in 27.6%. Renal and neurological involvement were more frequent in positive ANCA patients (p=0.005) and cardiac involvement in ANCA negative (p=0.001). Chest-x-ray showed lung infiltrates (56.3%) and nodules (16%). Eosinophilia was present in all cases. Serum IgE levels were raised in 73.3% of tested patients. A total of 101 biopsies were done (25 nerve, 15 lung, 6 renal, 7 nasal, 38 skin, 4 bowel, 2 pericardial, 2 liver, 2 pleural) and showed eosinophil infiltrates in 52 cases and necrotizing vasculitis in 47. Oral prednisone (1mg/kg) was given to all patients, iv metilprednisolone to 45%, iv cyclo-phosphamide (CF) to 41.4%, oral CF to 24.1%, azathioprine to 21.8%, and mycophenolate to 5.7%. Rituximab was successfully administered in 2 cases with refractory disease. Leukopenia was more frequent in patients treated with oral CF (p<0.000). During the follow-up, 27.6% patients developed bacterial infections, 11.5% opportunistic infections and 9 (10.3%) died. Dead was mainly related to infections (p=0.011) and refractory disease. EGPA patients had less renal involvement (p=0.005) and more cardiac involvement (p=0.002) than those with GPA and MPA and a lower mortality (p=0.001) Conclusions: patients with EGPA have less severe clinical manifestations than those with GPA and MPA and a lower mortality. Renal involvement is rare and cardiac involvement frequent, as previously described. Most patients with FFS>1 improve with corticosteroids and CF. RTX may be useful in patients with refractory disease. The overall EGPA survival rate is good and dead is mainly related to infections and refractory disease Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4714